(untitled) (Research, Society and Development, 2020)
The World Health Organization reports that one of the main causes of metabolic diseases and deaths is overweight and obesity. Resistance training is one of the allies for the prevention and reduction of body fat, making it possible to reduce the percentage of fat and increase muscle mass. Due to this fact, the objective was to evaluate the fat percentage index, body mass index and waist-hip ratio, in resistance training practitioners and to compare to sedentary people. Sixty male volunteers were included in the study, being divided into two groups: group of sedentary men 30 volunteers and the group of men practicing weight training composed of 30 volunteers. The results after evaluating the group of sedentary men and group of men who practice bodybuilding, demonstrated that the group of sedentary people have the average value of fat percentage above the bodybuilders. And it can be concluded that the practice of weight training can directly influence the body composition of the practitioners, reducing the percentage of fat and the ratio of waist to hip ratio (WHR).